Klausa Verbal dalam Cerpen Imraatun Ghalabat al-Syaithan Karya Taufiq al-Hakim (Arabic Syntax Study): Klausa Verbal dalam Cerpen Imraatun Ghalabat al-Syaithan Karya Taufiq al-Hakim (Arabic Syntax Study) - Fadilla, Audryane Anindita; Rohanda, Rohanda; Pauji, Resa Restu (LP2M IAIN Sultan Amai Gorontalo, 2026)
Background: Human communication, whether spoken or written, is fundamentally structured around clauses, with verbal clauses holding particular significance. This is equally true in literary works, where the complexities of verbal clauses given their varied types and functions are prominently displayed. Consequently, investigating these clauses is essential for a deeper comprehension of syntactic structures. Aims: This study aims to identify the types of verbal clauses based on their internal structure and their position within sentences, and to determine their functions in the source text. Methods: Employing a qualitative content analysis method, this research focuses on verbal clauses as the unit of analysis. The data source is the short story